The effect of orthognathic surgery on the temporomandibular joint and oral function: a systematic review. Issue 5 (May 2017) - te Veldhuis, E.C.; te Veldhuis, A.H.; Bramer, W.M.; Wolvius, E.B.; Koudstaal, M.J.
Abstract: The objective of this systematic review was to examine the effect of orthognathic surgery (OS) on the temporomandibular joint and oral function. Electronic databases were systematically searched for studies published until October 2015. Articles were assessed against predefined inclusion criteria. The included papers were divided into four groups based on the type of OS performed. The following items were recorded: quality of evidence using the Oxford Centre for Evidence-Based medicine (CEBM) criteria, number of patients, presence/absence of controls, mean age at treatment, follow-up time, clinical examination findings, bite force, use of the Helkimo Index and Research Diagnostic Criteria for Temporomandibular Disorders, imaging findings, and patient questionnaire results. A total of 4669 articles were identified; 76 relevant articles were included in the review. These studies assessed a total 3399 patients and 380 controls, with a mean age of 25.4 years. The great variety of OS techniques, examination techniques, diagnostic criteria, and imaging techniques used in the articles studied, as well as the quality of the study designs, made it difficult to compare studies and to draw conclusions. However, looking at the different aspects studied in general, it can be stated that OS seems to have little or no harmful effect on the TMJ and oral function (level of evidence: levels II, III, and IV).